Assessment of Fisheries and Management- Insights from Dal Lake, Kashmir - Mir, Shakir Ahmad; Ojha, Shekhar Nath; Ananthan, Pachampalayam Shanmugam; Qureshi, Neha Wajahat; Argade, Shivaji Dadabhau; Gul, Shahid; Thangavel , Velumani (Indian Journal of Extension Education, 2022)
The present study was done during 2019-20 to assess the current fisheries status of Dal lake in terms of species diversity, trophic status, trends and patterns in fish catch, the lake’s physicochemical properties and its management. Shannon-Wiener index used to calculate the species diversity was 2.08 with the species evenness value of 2.19. The water quality analysis revealed that the lake is highly polluted due to various anthropogenic activities like sewage influx, vegetable cultivation, tourism activities, etc. The lake is dominated by omnivorous fishes followed by herbivores and carnivores. The compound annual growth rate results from 1989 to 2019 for capture fisheries showed the positive growth rate of 0.23. A lack of coordination between the different governing bodies has led the Dal lake to its brim of death. It is recommended to restore by controlling the sewage influx and weed growth. Additionally, the existing pattern of governance and management needs to be modified.
Keywords: Assessment; Governance; Shannon-Weiner index; Dal lake; Kashmir